Evolutionary analysis and structural characterization of Aquilaria sinensis sesquiterpene synthase in agarwood formation: A computational study. (7th November 2018) - Liu, Yong; Chen, Jingan; Qian, Jieying; Lin, Hao; Sun, Ning; Huang, Zunnan
Highlights: Analysis of evolutionary history showed that AsSTS diverged early in angiosperms. New conserved motif (RXR) was predicted in AsSTS. 23 positively selected sites and three positively selected branches were detected. 403D, 412P, 470G and 538S were shown to affect the function and stability of AsSTS. Three virtual mutants (D403R, G470Q and S538K) were evaluated to stabilize AsSTS. Abstract: Agarwood originating from Aquilaria sinensis contains sesquiterpenoids that have tremendous commercial value in the pharmaceutical and fragrance industries. Aquilaria sinensi s sesquiterpene synthase (AsSTS) is the key enzyme in the agarwood biosynthesis pathway, and its activity directly affects the chemical composition of agarwood; however, its role in species evolution remains unclear. In this study, we performed an evolutionary analysis based on 68 plant sesquiterpene synthase (STS) genes and further structural characterization of the gene encoding AsSTS to explore its molecular evolution. The phylogenetic tree indicated that these STS genes included three subfamilies. Additionally, 23 positively selected sites were detected, and no influence of recombination was found. Furthermore, the protein structure of AsSTS was characterized using primary sequence and structural analyses as having a functional active site lid domain, a substrate binding site, two post-translational modification sites and four conserved motifs. Finally, most virtual mutations of positively selected sites could be stabilized against thermal denaturation by a decrease in free energy, and three virtual mutations (D403R, G470Q and S538K) were shown to play important roles in the function and stability of AsSTS. The molecular evolutionary analysis of plant STSs provides essential clues for further experimental site-directed mutagenesis and molecular modification of AsSTS.